Penggunaan Media Sosial Instagram Unifa sebagai Sarana Informasi Penerimaan Mahasiswa Baru - Rara Madika Banne; Angel DJ; Reyhan Zakiah Padhil; Amalia Zul Hilmi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to analyze how Universitas Fajar (Unifa) utilizes Instagram as a communication tool to deliver information regarding New Student Admissions (Penerimaan Mahasiswa Baru/PMB). The focus of this research encompasses the Integrated Marketing Communication (IMC) strategy applied through five elements: advertising, public relations, direct marketing, digital marketing, and sales promotion. The research method employed is descriptive qualitative, with data collected through in-depth interviews with social media managers and public relations staff, as well as observations of the university’s official Instagram content.The findings indicate that Unifa implements advertising through paid Instagram ads to broaden the reach of information across various regions in Sulawesi. Public relations strategies are carried out by maintaining timely publication and consistency in the campus’s visual identity, ensuring messages are professional and reinforce brand image. Direct marketing is evident in the form of responsive two-way communication in comment sections and direct messages, while digital marketing is optimized through the use of hashtags, collaborations among departmental accounts, and paid content optimization. Sales promotion strategies include offering scholarships, tuition discounts, and enrollment wave promotions as additional incentives for prospective students.These findings confirm that the effective implementation of an integrated communication strategy not only enhances campus visibility but also builds trust, interaction, and brand awareness among prospective students. The study recommends more consistent and responsive social media management to further optimize promotional strategies.